Discourse Markers in English and Lithuanian - Masaitienė, Dalia (Kalbotyra, 2003)
The paper is devoted to a contrastive analysis of the use of discourse markers in English and Lithuanian everyday conversation. Though the status of discourse marker in English has not yet been fully clarified, it has been widely discussed. In Lithuanian, however, no attempts have been made to delimit this category: There is a wide range of words and phrases that could be interpreted as discourse markers in both languages. Their main function is to indicate an interactive relationship between the participants of conversation. The study is carried out analysing transcribed conversations in English and Lithuanian. Discourse markers in both languages are mostly words with little lexical meaning that appear on the periphery of clause structure. In both languages, discourse markers can form a separate tone group or be part of a larger unit. Some markers appear to be semantic and functional equivalents of their counterparts in the other language while some do not have equivalents. A number of Lithuanian markers can be used only in a very informal setting, which presupposes more monitoring of speech and, consequently a greater variation in usage, depending on the level of formality of the situation.